Data Analysis Environment for X-ray Free-Electron Laser Experiments at SACLA. Issue 1 (2nd January 2017) - Joti, Yasumasa; Nakajima, Kyo; Kameshima, Takashi; Yamaga, Mitsuhiro; Abe, Toshinori; Okada, Kensuke; Sugimoto, Takashi; Hatsui, Takaki; Yabashi, Makina
Abstract : X-ray free-electron lasers (XFELs) with full spatial coherence, extreme brilliance, and ultra-fast pulse duration [1, 2 ] allow the investigation of complex phenomena in physics, chemistry, and biology with angstrom and femtosecond resolutions. In particular, a concept of "diffraction before destruction" [3 ] has been demonstrated for serial femtosecond crystallography (SFX) [4, 5 ] and coherent diffractive imaging (CDI) [6 ]. Using femto-second XFEL pulses, diffraction data are collected before radiation damage to samples has time to occur. Since samples are exchanged for each XFEL pulse, shot-to-shot data acquisition (DAQ) is mandatory to correlate the recorded data with the sample characteristics. The shot-to-shot DAQ must be synchronized with the repetition rate of the XFEL source, typically several tens to one hundred Hz for the machine based on normal-conducting accelerators. Shot-to-shot recording of XFEL pulse characteristics is also essential because they fluctuate due to the stochastic nature of a self-amplified spontaneous emission (SASE). We must carefully analyze a huge data set taking the fluctuation into account.